Pengaruh Rasio Kas dan Rasio Cepat terhadap Return on Assets pada CV. Graha Mineral Kota Sibolga - Ferdina Zai; Hadijah Sipahutar; Yusi Tri Utari Panggabean (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
Cash Ratio and Quick Ratio are important indicators in assessing a company’s ability to meet short-term obligations and utilize its assets efficiently. This study aims to examine the effect of Cash Ratio and Quick Ratio on Return on Assets (ROA) at CV. Graha Mineral Sibolga City during the period 2020–2024. The data were obtained from the company’s financial statements and analyzed using a quantitative method with multiple linear regression approach. Classical assumption tests, including normality, multicollinearity, autocorrelation, and heteroscedasticity tests, were conducted to ensure the validity of the model, while t-test and F-test were used to examine partial and simultaneous effects. The results showed that the average Cash Ratio was 154.36% with a range of 150.00%–160.00%, the Quick Ratio averaged 2.06 with a range of 1.88–2.30, and ROA averaged 14.58% with a variation of 14.49%–14.60%. The regression analysis indicated that partially, the Cash Ratio had a positive effect on ROA with a coefficient of 0.007, while the Quick Ratio had a negative effect with a coefficient of -0.171. However, the t-test results showed that both variables had no significant effect on ROA, with significance values of 0.498 and 0.458, respectively. Simultaneously, the F-test also indicated that Cash Ratio and Quick Ratio did not have a significant effect on ROA, with a significance value of 0.662. The coefficient of determination (R²) of 0.338 indicates that 33.8% of the variation in ROA is explained by these variables, while the remaining 66.2% is influenced by other factors outside the research model.